Ethnic differences in gross motor skills among indigenous Dayak children in Indonesia: a cross-sectional comparative study - Syarif, Indera; Habibie, Muhammad; Amalia, Bonita; Kumar, Parveen (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2026)
Background: Cultural movement exposure has been suggested as a potential factor influencing children’s motor development; however, empirical evidence on ethnic variation in gross motor skills among Indonesian children—particularly within indigenous Dayak sub-ethnic groups—remains limited. Objectives: This study aimed to examine differences in gross motor skills between Dayak Ngaju and Dayak Bakumpai children aged 8-11 years. Methods: A cross-sectional comparative design was employed involving 94 elementary school children (48 boys and 46 girls) from eight schools. Gross motor skills were assessed using the Indonesian-adapted TGMD-3, with established content validity (CVI = 0.91) and inter-rater reliability (ICC = 0.89). Performances were video-recorded and evaluated by trained raters blinded to participant identity. Two-way ANOVA was used to examine the effects of ethnicity and gender, with non-parametric tests applied when assumptions were violated. Results: No significant main effects of ethnicity or gender were found for locomotor, object control, or total TGMD-3 scores (p > 0.05). However, a significant ethnicity × gender interaction was observed for locomotor skills (p < 0.05). At the task level, a significant difference was identified only in boys’ horizontal jump performance, with Dayak Bakumpai boys scoring higher than their Ngaju counterparts. No other significant differences were observed across skill domains. Conclusion: Ethnic differences in gross motor skills among Dayak children appear to be limited and task-specific rather than consistent across domains. Cultural movement exposure may be associated with certain aspects of motor performance; however, causal interpretations cannot be established. These findings highlight the importance of context-sensitive physical education approaches that consider local movement practices without assuming generalised group differences.